Herrnhuutlase Michael Peterseni reisipäevikust: Herrnhaagist Eestimaale ja tagasi, 1742-44 - Ilja, Voldemar (Usuteaduslik Ajakiri, 2001)
From Herrnhagen, Germany, to Estonia and Back, 1742-44: The Travel Diary of Brother Michael Petersen. By Voldemar Ilja Michael Petersen was one of the 200 Herrnhut brothers and sisters who journeyed to Livonia or Estonia from 1729 to 1763 to preach Gospel and teach children. He started his diary on April 17, 1942, in Herrnhagen, where he and six more brothers were ordered to travel to Tallinn. They took a ship from Lubeck and arrived in Tallinn on June 26. For Michael Petersen, the first place to go was Vormsi island where he worked with local pastor named Holming and taught local Swedish children. In the beginning of 1743 Petersen was ordered to go to Kriimani in South-Estonia. There he acted as an accountant in a store and assisted at the building of local watermill. At the same time he had several confrontations with state officials, because the state did not favor religious movements that sounded radical or separatist. In January 1744 he caught an eye disease and felt homesick, so he started to make plans to return to Germany. Before departure he once more visited Vormsi — the place had become especially close to him. On February 27 he started his journey to Germany, traveled through Riga, Königsberg, and Lubeck, and arrived at Herrnhagen on April 30.